Effects of Lead Exposure in Wild Birds as Causes for Incidents and Fatal Injuries - Ivanka Lazarova; Gergana Balieva (Diversity, 2025)
Lead is among the most toxic heavy metals, posing significant risks to all living organisms. It is a pervasive and persistent contaminant in the environment. Ingested lead in birds and wildlife induces a range of sublethal effects that disrupt physiological functions and behavior, ultimately resulting in mortality at higher doses or with prolonged exposure. To investigate the relation of lead to accidents and injuries in wild birds, we analyzed lead concentration in 43 wild birds that were admitted as patients to the Wildlife Rehabilitation and Breeding Center (WRBC). The findings reveal a significant dependency between the detected levels of lead in the birds’ bone samples and the reported etiology of their injuries, with variances in the age groups of the patients received at the WRBC in Bulgaria.